Influência do Levamisol na resposta imune humoral anti-rábica em bovinos - Cazella, Luciane Neris (2009)
The aim of this study was to evaluate the effect of levamisole on the antirabies humoral immune response in bovines primovaccinated against rabies. Forty-two bovines, about twelve months old, were randomly divided into three groups. Animals from VL group received one dose of levamisole and antirabies vaccine on day zero. Cattle from group V7L received one dose of antirabies vaccine on day zero and, on day seven, one dose of levamisole. Bovines from control group (GC) were immunized with just one dose of antirabies vaccine on day zero. A lyophilized, inactivated rabies vaccine, developed at Instituto Butantan was used. Blood samples were taken on days zero, 30 and 60. The neutralizing antibody titers were determined by serum neutralization in BHK21 cells, based on the Rapid Fluorescent Focus Inhibition Test (RFFIT) and on the Fluorescent Inhibition Microtest (FMIT). The results obtained showed that there was not significant difference in neutralizing-antibody titers and neither in the frequency of immunized animals between groups treated and not treated with levamisole 30 and 60 days after antirabies vaccination. In conclusion, levamisole administration (6.0 mg/kg of body weight) in primovaccinated bovines against rabies did not influence the antirabies humoral immune response.